Strengthening Wood Structures Against Climate Change: Approaches from Türkiye and Different Countries - Öztürk, İbrahim Engin; Altay, Çağlar; Gençdağ Gözen, Esra (Bartin Orman Fakültesi dergisi, 2025)
This study examines the durability and strengthening strategies of wooden structures in Türkiye against climate change and extreme weather conditions. The effects of climate change challenge the resistance of structures to fire, water and other natural events. Although wood continues to be used as a traditional building material, it needs to be adapted to these new conditions. Wood that is not protected in any way will deteriorate, change shape, crack, develop dimensional differences, change colour, lose gloss, increase surface roughness and lose properties with similar negative effects over time due to climate change and weather conditions. This study discusses fire and water protection strategies, material renewal techniques and sustainability enhancement methods to assess the current status of wood structures in Türkiye, Canada and Finland and their durability against climate change. The study provides suggestions to ensure the sustainability of both existing and newly constructed wood structures against climate change. In addition, this article provides important information from studies in the literature on how to protect and develop wood structures against climate change in the modern world, and discusses new protection strategies against ever-changing climate differences.